Mucosal distribution of somatostatin-secreting gastric Delta cells in children with gastrointestinal reflux diseases - Kim, Dong-Uk; Na, Jae Yoon; Paik, Seung Sam; Jee, Seungyun; Lee, Young Ho; Kim, Yong Joo (Frontiers in Pediatrics, 2023)
Introduction: Gastric delta cells (D-cells) secrete somatostatin, which is the primary paracrine suppressor of acid secretion. The number and distribution of D-cells were investigated in children exhibiting endoscopic findings of duodenogastric and gastroesophageal reflux. This study aimed to determine whether the number of D-cells in the gastric body differs from that in the gastric antrum in children using endoscopic findings.We retrospectively used immunohistochemical assessments to determine the number of Dcells in the gastric body and antrum in 102 children who presented with abdominal symptoms. The number and distribution of D-cells were investigated according to symptoms, endoscopic findings of gastroesophageal reflux and duodenogastric reflux, and Helicobacter pylori infection status.The average age of the patients was 13.3 ± 3.3 years, and the male-to-female ratio was 1:1.68. The mean number of D-cells per high-power field in the antrum and body did not significantly differ by symptoms. However, these values were significantly lower in the gastric body than in the antrum for all symptoms (p < 0.05). Children with reflux had a higher mean number of D-cells (9.6 ± 8.8) in the gastric body than did those without reflux (4.3 ± 3.4) (p = 0.007). Furthermore, the number of Dcells in the gastric body was marginally significantly lower in Helicobacter pylori-positive children (4.9 ± 6.5) than in Helicobacter pylori-negative children (8.5 ± 8.2) (p = 0.053).The number of D-cells in the gastric body decreased in Helicobacter pylori-positive children but significantly increased in children with duodenogastric reflux. Therefore, somatostatin peptide secretion by D-cells may be a major pathophysiological pathway in gastrointestinal reflux disease.